Conduit quality control protocol in CABG - Del Río, Ignacio Juárez; Medinilla, Enrique Villagrán; Albarrán, Ali Ayaon; Rubio Alonso, Miguel Angel; Peinado, Angel Aroca (Journal of Cardiology and Cardiovascular Medicine, 2023)
Cardiac revascularization surgery has a long history. Its results and safety are well known. Nonetheless, the long-term patency rate of certain grafts used in cardiac revascularization is non-optimal, and CABG is associated with a risk of cerebrovascular stroke due to aortic manipulation. We have developed a simple control quality protocol of the anastomosis performed in CABG, aiming to improve the long-term patency of certain grafts used in cardiac revascularization surgery and reduce the risk of cerebrovascular stroke in those patients.